'No one prepared me to go home': Cerebrovascular accident survivors' experiences of community reintegration in a peri-urban context - Pragashnie Govender; Deshini Naidoo; Kiara Bricknell; Zainab Ayob; Holly Message; Sibongiseni Njoko (AOSIS, 2019)
Background: The South African health system has policies and strategies to ensure effective rehabilitation and reintegration of individuals who have survived a cerebrovascular accident into their respective communities. However, implementation of such guidelines remains an issue. Aim: This study sought to explore cerebrovascular accident (CVA) survivors' experiences of community integration. Setting: The study was located in a peri-urban community within the KwaZulu-Natal Province, South Africa. Methods: An explorative qualitative study with eight purposively selected CVA survivors was conducted via semi-structured individual interviews. Data were audio-recorded and manually transcribed prior to thematic analysis. Trustworthiness of the study was maintained by strategies such as analyst triangulation, an audit trail and use of thick descriptions. Ethical principles of autonomy, informed consent, confidentiality and privacy were also maintained in the study. Results: Six themes emerged that highlighted (1) loss of autonomy and roles, (2) barriers to community reintegration, (3) social isolation of participants, (4) finding internal strength, (5) enablers of community reintegration including the positive influence of support and the benefits derived from rehabilitation and (6) recommendations for rehabilitation. Conclusion: The study revealed both positive and negative influences that impact CVA survivors' ability to effectively reintegrate into their respective communities following a CVA. Recommendations include the need for education and awareness around access to rehabilitation services for CVA survivors, advice on how to improve CVA survivors' ability to mobilise in the community and make environmental adaption to facilitate universal access, provision of home programmes and caregiver training for continuity of care and for inclusion of home-based rehabilitation into current models of care.